Foamquake: A Novel Analog Model Mimicking Megathrust Seismic Cycles. Issue 3 (24th February 2022) - Mastella, G.; Corbi, F.; Funiciello, F.; Rosenau, M.
Abstract: In the last decades, seismotectonic analog models have been developed to better understand many aspects of the seismic cycle. Differently from other lab‐quake experiments, seismotectonic models mimic the first order characteristics of the seismic cycle in a scaled fashion. Here we introduce Foamquake : A novel seismotectonic model with a granular frictional interface that as a whole behaves elastoplastically. The model experiences cycles of elastic loading and release via spontaneous nucleation of frictional instabilities at the base of an elastic foam wedge, hereafter called foamquakes. These analog earthquakes show source parameters (i.e., moment‐duration and moment‐rupture area) scaling as great interplate earthquakes and a coseismic displacement of few tens of meters when scaled to nature. Models with two asperities separated by a barrier can be performed with Foamquake given the 3D nature of the setup. Such model configuration generates sequences of full and partial ruptures with different recurrence intervals as well as rupture cascades. By tuning the normal load acting on individual asperities, Foamquake reproduces superimposed cycles rupture patterns such as those observed along natural megathrusts. The physical properties of asperities and barriers affect model seismic behavior. Asperities with similar properties and low yield strength fail preferentially in a simultaneous manner. The combination of all those characteristics suggests that Foamquake is a valuable tool for investigating megathrust seismicity and seismic processes that depend on the 3D nature of the subduction environment. Plain Language Summary: Despite earthquakes rank within the main geohazards, there are still several important open questions about their nature that remain unanswered or require additional investigation. Complementary to observational studies, a strategy often used by scientists to tackle this problem is to safely reproduce earthquakes with computer simulations or with laboratory experiments. Here we introduce a novel experimental model ( Foamquake ) that reproduces the largest earthquakes on Earth, those that occur at convergent plate boundaries like the Tohoku‐oki earthquake that hit the Japanese Pacific coast in 2011. Our model has the distinctive characteristic of reproducing earthquakes in a scaled fashion; that is, lengths, velocities and forces are smaller but scaled with respect to real ones. Moreover, time is accelerated with regard to nature so that we do not wait hundreds of years to observe a lab‐quake. Indeed, we are able to study the details of hundreds of them in a few minutes long experimental run. We report the details of the experimental model and focus on the arguments bringing us to consider our lab‐quakes similar to real earthquakes. We demonstrate that the experimental setup can afford new insights for understanding the seismic behavior at convergent plate boundaries. Key Points: A novel seismotectonic model that reproduces realistically several characteristics of great subduction megathrust earthquakes is presented Analog earthquakes follow similar source parameters scaling as natural interplate earthquakes Along trench segmentation introduces complexity in space‐time‐rupture history, highlighting the importance of the 3D nature of the setup